2022
DOI: 10.1515/phys-2022-0051
|View full text |Cite
|
Sign up to set email alerts
|

Magnetofluid unsteady electroosmotic flow of Jeffrey fluid at high zeta potential in parallel microchannels

Abstract: In this article, the magnetofluid unsteady electroosmotic flow (EOF) of Jeffrey fluid with high zeta potential is studied by using the Chebyshev spectral method and the finite difference method. By comparing the potential distribution and velocity distribution obtained by the Chebyshev spectral method and finite difference method, it is concluded that the Chebyshev spectral method has higher precision and less computation. Then the numerical solution obtained by the Chebyshev spectral method is used to analyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…The EO peristaltic flow of MHD Jeffery nanofluid was published by Rafiq and coworkers [25] and found to have potential applications in food diagnosis, drug delivery, etc. Ren et al [26] demonstrated the EOF of MHD Jeffery fluid in parallel microchannels. The EO Enhanced MHD Third-grade fluid application for blood flow in arteries was examined by Choudhari et al [27].…”
Section: Introductionmentioning
confidence: 99%
“…The EO peristaltic flow of MHD Jeffery nanofluid was published by Rafiq and coworkers [25] and found to have potential applications in food diagnosis, drug delivery, etc. Ren et al [26] demonstrated the EOF of MHD Jeffery fluid in parallel microchannels. The EO Enhanced MHD Third-grade fluid application for blood flow in arteries was examined by Choudhari et al [27].…”
Section: Introductionmentioning
confidence: 99%